Digital Holocaust memory, education and research - Walden, Victoria (Springer International Publishing AG, 2021)
Intro -- Contents -- Notes on Contributors -- List of Figures -- List of Tables -- Defining the Digital in Digital Holocaust Memory, Education and Research -- Structure of This Book -- References -- Part I: (New) Dimensions in Testimony -- Virtually Part of the Family: The Last Goodbye and Digital Holocaust Witnessing -- Performing the Witness -- Performing the Family -- The Last Goodbye VR Experience -- The Witnessing Text -- Conclusion -- References -- Realms of Digital Memory: Methodological Approaches to 360° Testimony on Location -- The Last Goodbye -- An Empathy Machine? -- Methodological Considerations of 360° Testimony on Location -- 360° ToL: Life Histories -- 360° ToL: Location Vignettes -- Preparing for the Testimony Collection -- 360° ToL Testimony Collection Process -- Laser Scanning and Photogrammetry -- The Current 360° ToL Collection -- Volumetric Oral History -- Conclusion -- References -- The Production of German- and Russian-Language Interactive Biographies: (Trans)National Holocaust Memory between the Broadcast and Hyperconnective Ages -- The Holocaust Archive in a Hyperconnected and Transnational Age -- Theoretical and Ethical Implications for Dimensions in Testimony in the Russian- and German-Speaking Context -- Pre-Production Process -- Production Process -- Post-Production Process -- Conclusion -- References -- Part II: (Web)sites of Memory -- MEMOZE: Memory Places, Memory Spaces: 'Glocal' Holocaust Education through an Online Research Portal -- MEMOZE: Modern Mediation Strategies of Testimony and Space -- Project Context -- The Online Research Portal: Technical Properties, Design and Conception -- The Space of Memory -- The Space of Transfer -- The Space of Transgenerational Dialogue -- The Room of Names -- Empty Spaces -- The Cultural Space -- Conclusion -- References.